Pharmacokinetics, Metabolism and Bioavailability of the New Anti-allergic Drug BM 113 - Duchêne, Patrick; Tran, Gilles; Ladure, Philippe; Ollivier, Roland; Buzas, André; Merour, Jean-Yves; Houin, Georges (Arzneimittelforschung, 1999)
A new anti-allergic drug, BM 113 (1-(benzhydryloxyethyl)piperidino-4-ethylacetate, CAS 115313-90-1; BM 113 maleate: CAS 115313-91-2) with a piperidinic structure, showing anti-histaminic properties was studied in male and female Sprague-Dawley rats after i.v. or p.o. administrations of 0.750 mg/kg 3H-BM 113. This product presented a rapid faecal elimination after i.v. and oral administration. The total recovery of the dose was obtained after 144 h. Biliary elimination was very fast: 54% of the intravenous dose were biliarily eliminated within 2 h, essentially as a conjugated form. For both i.v. and p.o. routes, the blood kinetics were biexponential. Intravenous administration led to elimination half-lives of 1.36 h and 0.75 h for the first phase and 38.6 h and 56.5 h for the second one for males and females, respectively. After oral administration, rebounds corresponding to the presence of enterohepatic cycle or metabolites were observed. Thus, the determination of half-lives was not possible. Slight but significant differences of some pharmacokinetic parameters were observed between genders. The results obtained during the protein binding study corresponded to the BM 113 metabolite known as BM 212. The free fraction corresponded to 55.5%.Tissular concentrations showed a rapid distribution of 3H-BM 113 followed by a slow elimination. In most of the tissues, the decrease was biexponential. The organs containing most of the radioactivity were those of the intestinal tract and the liver. Other tissues presented concentrations close to those of plasma. Lipidic tissues, showing low BM 113 concentrations, presented a slower elimination, probably related to the high lipophilicity of molecule.
Keywords: Antiallergic drugs; 1 -(Benzhydryloxyethyl)piperidino-4-ethylacetate; BM 113, pharmacokinetics, rat, tissue distribution; CAS 115313-90-1; CAS 115313-91-2